2010
DOI: 10.1002/pbc.22481
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of chronic idiopathic thrombocytopenic purpura

Abstract: The most relevant risk factors for the development of chronic ITP included a gradual mode of onset of symptoms over more than 2 weeks period, initial platelet count >20 x 10(9)/L, and age more than 10 years at presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 25 publications
3
39
2
Order By: Relevance
“…The mean platelet count at time of diagnosis was calculated in 12 studies. 19,20,23,24,26,27,29,30,37,[41][42][43] A significantly higher platelet count at diagnosis was found in patients who developed chronic ITP, with a mean difference 5.27 (95% CI 2.69-7.86). Four articles calculated a median platelet count, and 1 found significantly higher median platelet counts at diagnosis in patients who developed chronic ITP.…”
Section: Laboratory Measurementsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mean platelet count at time of diagnosis was calculated in 12 studies. 19,20,23,24,26,27,29,30,37,[41][42][43] A significantly higher platelet count at diagnosis was found in patients who developed chronic ITP, with a mean difference 5.27 (95% CI 2.69-7.86). Four articles calculated a median platelet count, and 1 found significantly higher median platelet counts at diagnosis in patients who developed chronic ITP.…”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…[19][20][21][22]29,[32][33][34]36,39,41,43,44 Preceding infections and vaccinations. Seven studies analyzed whether an infection before the onset of ITP was correlated with development of chronic ITP 19,22,23,29,30,32,37 ; 4 studies evaluated the occurrence of viral infections only. 21,33,34,36 A preceding vaccination was evaluated in 3 studies, 18,22,30 and 2 articles reported the incidence of a preceding infection or vaccination as one combined predictor.…”
Section: Clinical Predictorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The severity of thrombocytopenia associated to some extent but not completely with the propensity to bleed which necessitates more factors to be evaluated [28,29]. On the other hand, increased platelet antibodies level is only one of several factors involved in development of the clinical status of ITP.…”
Section: Discussionmentioning
confidence: 99%